2022
DOI: 10.1111/jan.15465
|View full text |Cite
|
Sign up to set email alerts
|

Associations among disability, depression, anxiety, stress, and quality of life between stroke survivors and their family caregivers: An Actor‐Partner Interdependence Model

Abstract: Aim: To explore the effects of disability, depressive, anxiety and stress symptoms on patients' and their partners' quality of life (QoL) using the actor-partner interdependence model (APIM). Design:A cross-sectional study using actor-partner interdependence model. Methods:We recruited 183 dyads of stroke survivors and their family caregivers in Indonesia. The World Health Organization Disability Assessment (WHODAS 2.0), Depression, Anxiety and Stress (DASS-42) and Rand Short Form Health Survey (SF-36) were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 63 publications
(87 reference statements)
0
9
0
1
Order By: Relevance
“…Stroke is the most common cause of death and disability worldwide (Feigin et al, 2017; GBD 2019 Stroke Collaborators, 2021; Thayabaranathan et al, 2022). About 80% of stroke survivors have upper limb motor impairment (4), which seriously affects their activities of daily living and quality of life (Pollock et al, 2014;Stinear et al, 2020;Schindel et al, 2021;Yuliana et al, 2022). Studies have shown that upper extremity recovery is faster in patients with subacute stroke than in those with chronic periods (Dobkin and Carmichael, 2016;Bernhardt et al, 2017), making the subacute period an essential period for upper extremity rehabilitation in stroke (Dobkin and Carmichael, 2016;Bernhardt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is the most common cause of death and disability worldwide (Feigin et al, 2017; GBD 2019 Stroke Collaborators, 2021; Thayabaranathan et al, 2022). About 80% of stroke survivors have upper limb motor impairment (4), which seriously affects their activities of daily living and quality of life (Pollock et al, 2014;Stinear et al, 2020;Schindel et al, 2021;Yuliana et al, 2022). Studies have shown that upper extremity recovery is faster in patients with subacute stroke than in those with chronic periods (Dobkin and Carmichael, 2016;Bernhardt et al, 2017), making the subacute period an essential period for upper extremity rehabilitation in stroke (Dobkin and Carmichael, 2016;Bernhardt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…1 Strok menyebabkan ketergantungan pasien terhadap orang lain yang berdampak pada penurunan kualitas hidup. 2 Pada tahun 2015, jumlah kematian akibat strok berada pada urutan kedua setelah penyakit jantung iskemik. 3 American Heart Association mencatat sebanyak 17 juta kasus strok dan 6,6 juta kematian terjadi di berbagai negara pada tahun 2019.…”
Section: Pendahuluanunclassified
“…People with stroke often have long-lasting rehabilitation needs, and recovery is known to be complex, with several care providers involved [7][8][9]. The effects of stroke can be profound and lead to a range of activity and participation limitations [9][10][11], such as reduced quality of life, social isolation [12][13][14] and adverse events such as falls [9,15]. Many patients and families describe the support post-stroke as poor and not patient-centred [16][17][18] and report poor engagement in their care and treatment decisions [7,19].…”
Section: Introductionmentioning
confidence: 99%